TRENDS AND DETERMINANTS OF THE GEOGRAPHIC DISTRIBUTION OF ECONOMIC ACTIVITIES: EVIDENCE FROM INDONESIAN MANUFACTURING - Khoirunurrofik, Khoirunurrofik (Journal of Indonesian Applied Economics, 2017)
The paper analyzes the trends and determinant factors vis-Ã -vis spatial distribution in Indonesian manufacturing during the period of 1990â€“2010. There is a long-term increasing trend of regional specialization driven by core regions within Java and by affluent regions outside of Java. Among resource-based and labor-intensive industries, there is a smoothly declining trend of geographic concentration. An increasing trend in regional specialization and geographic concentration during the economic crisis is identified, which turns into a decreasing trend at the onset of setting up a decentralization policy and then again pushed upward. Finally, by applying spatially weighted Ellison-Glaeser (EG) Index, it is found that labor skills, export activities, and wage rates strongly determine the degree of agglomeration among Indonesian manufacturing industries.Keywords: Agglomeration, Asian financial crisis, decentralization, regional specialization, geographic concentration, global economy.JEL: R11, R12, R14,R30